Simultaneous biofortification of rice with zinc, iodine, iron and selenium through foliar treatment of a micronutrient cocktail in five countries - Prom-u-Thai, Chanakan; Rashid, Abdul; Ram, Hari; Zou, Chun-Qin; Guilherme, Luiz Roberto Guimaraes (Frontiers Media, 2020)
Widespread malnutrition of zinc (Zn), iodine (I), iron (Fe) and selenium (Se), known as hidden hunger, represents a predominant cause of several health complications in human populations where rice (Oryza sativa L.) is the major staple food. Therefore, increasing concentrations of these micronutrients in rice grain represents a sustainable solution to hidden hunger. This study aimed at enhancing concentration of Zn, I, Fe and Se in rice grains by agronomic biofortification. We evaluated effects of foliar application of Zn, I, Fe and Se on grain yield and grain concentration of these micronutrients in rice grown at 21 field sites during 2015 to 2017 in Brazil, China, India, Pakistan and Thailand. Experimental treatments were: (i) local control (LC); (ii) foliar Zn; (iii) foliar I; and (iv) foliar micronutrient cocktail (i.e., Zn + I + Fe + Se). Foliar-applied Zn, I, Fe or Se did not affect rice grain yield. However, brown rice Zn increased with foliar Zn and micronutrient cocktail treatments at all except three field sites. On average, brown rice Zn increased from 21.4 mg kg–1 to 28.1 mg kg–1 with the application of Zn alone and to 26.8 mg kg–1 with the micronutrient cocktail solution. Brown rice I showed particular enhancements and increased from 11 μg kg–1 to 204 μg kg–1 with the application of I alone and to 181 μg kg–1 with the cocktail. Grain Se also responded very positively to foliar spray of micronutrients and increased from 95 to 380 μg kg–1. By contrast, grain Fe was increased by the same cocktail spray at only two sites. There was no relationship between soil extractable concentrations of these micronutrients with their grain concentrations. The results demonstrate that irrespective of the rice cultivars used and the diverse soil conditions existing in five major rice-producing countries, the foliar application of the micronutrient cocktail solution was highly effective in increasing grain Zn, I and Se. Adoption of this agronomic practice in the target countries would contribute significantly to the daily micronutrient intake and alleviation of micronutrient malnutrition in human populations.